Psychometric Validation of Nursing Student’s Learning Experiences Questionnaire on using Virtual Reality - Nia Ratnasari; Raini Diah Susanti; Hasniatisari Harun (Universitas Padjadjaran, 2023)
The use of virtual reality can provide a transformative learning experience for nursing students, which can be evaluated with an instrument. A valid and consistent instrument can provide correct data, so an instrument needs to be tested psychometrically so that the validity and consistency of the instrument can be known, especially on adapted instruments. The aim to translate and test the validity and reliability of the Indonesian version of the Web-Based Learning Tools (WBLT) Evaluation Scale. The research design used was descriptive-quantitative with a cross-sectional approach. The study population was undergraduate students of the Faculty of Nursing at Universitas Padjadjaran, with a total sample size of 104 through purposive sampling. The Web-Based Learning Tools were used, with validity and reliability testing using SPSS based on Pearson correlation values and Cronbach's alpha. The Pearson correlation test yielded results of r-count > 0.2279 and Cronbach's alpha test = 0.919. Based on the results of the study, the instrument has good validity and very high reliability. The Indonesian version of the WBLT instrument is valid and reliable, so further research can use the instrument to evaluate the use of virtual reality on the learning experience of nursing students.